2010
DOI: 10.1089/hum.2009.162
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Associated with Artemis Overexpression After Lentiviral Vector-Mediated Gene Transfer

Abstract: Artemis is a hairpin-opening endonuclease involved in nonhomologous end-joining and V(D)J recombination. Deficiency of Artemis results in radiation-sensitive severe combined immunodeficiency (SCID) characterized by complete absence of T and B cells due to an arrest at the receptor recombination stage. We have generated several lentiviral vectors for transduction of the Artemis sequence, intending to complement the deficient phenotype. We found that transduction by a lentiviral vector in which Artemis is regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 41 publications
4
32
0
Order By: Relevance
“…1B). Similar to our previous report, 18 in a 5-day survival study mouse 3T3 cultures transduced with both EF1a-Puro and PGK-Artemis remained viable at all vector doses ( p > 0.05 at an MOI of 10); however, a dose-dependent decrease in cell survival was observed for cultures transduced with EF1a-Artemis at increasing multiplicities of infection ( p < 0.05 vs. all other groups; Fig. 1B).…”
Section: Innate Regulation Of Artemis Prevents Artemis-mediated Cytotsupporting
confidence: 90%
See 4 more Smart Citations
“…1B). Similar to our previous report, 18 in a 5-day survival study mouse 3T3 cultures transduced with both EF1a-Puro and PGK-Artemis remained viable at all vector doses ( p > 0.05 at an MOI of 10); however, a dose-dependent decrease in cell survival was observed for cultures transduced with EF1a-Artemis at increasing multiplicities of infection ( p < 0.05 vs. all other groups; Fig. 1B).…”
Section: Innate Regulation Of Artemis Prevents Artemis-mediated Cytotsupporting
confidence: 90%
“…16 We subsequently demonstrated that overexpression of Artemis after lentiviral transduction is associated with cytotoxicity, a halt in cell cycle progression, and fragmentation of genomic DNA ultimately resulting in apoptosis. 18 These results, along with the previous reports demonstrating incomplete immune reconstitution of SCID-A after ex vivo transduction with an exogenous promoter, 16,17 emphasize the importance of providing Artemis expression at a level that is nontoxic and yet sufficient to correct the SCID-A T -B -phenotype. Accordingly, we isolated and characterized the human Artemis promoter (APro) as a sequence extending 1 kilobase upstream from the human Artemis translational start site on human chromosome 10.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations